THE DIFFERENCES IN COMPLETENESS AND TIMELINESS OF ELECTRONIC MEDICAL RECORD DOCUMENTATION IN NURSING WARDS: PERSPECTIVES FROM SURGICAL AND NON-SURGICAL DOCTORS - Asmiragani, Syaifullah; Sri Andarini; Viera Wardhani (Universitas Brawijaya, 2025)
The 2023 Quality Committee Report of Hospital X revealed lower levels of completeness and timeliness in the surgical ward, especially in the initial assessment, initial medical plan, and patient progress notes. Regarding this, the present study aims to analyze problematic Electronic Medical Records (EMR) components and the factors causing incompleteness and delay in data entry in surgeons and non-surgeons. This cross-sectional study was conducted by using 362 inpatient EMRs to analyze four key components, namely initial assessment, initial medical plan, Integrated Patient Progress Note (IPPN), and medical resume. Besides, 293 doctors completed questionnaires assessing their understanding of EMR-related regulations and their data entry timing for the four components. Completeness and timeliness analysis was performed using Chi-Square, while understanding of regulations and entry time was analyzed using Mann-Whitney. The findings indicated that non-surgeons showed higher completeness and timeliness in the initial assessment, medical resume, and CPPT (p<0.05), while surgeons excelled in the initial diagnostic plan in the initial medical plan (p<0.05). There was no difference in understanding of regulations, but non-surgeons took longer to enter data on assessment and initial medical plan (p<0.05). Finally, contributing factors include EMR technology, physician workflow, and physician interaction time with the EMR.